Early postoperative endoscopic sphincterotomy for retained biliary stones. - Bickerstaff, K; Berry, A; Chapman, R; Britton, J (1988)
Endoscopic sphincterotomy was attempted on 18 patients with retained biliary stones. Endoscopy was performed within 2 weeks of the operation in 13 patients and within 3 weeks in 5 patients. A T-tube was present in 14 patients and 6 patients had multiple stones. Sphincterotomy and complete duct clearance was achieved in 17 patients (94%) and a complication (haemorrhage) occurred in one patient (6%).